Kenabian dan Ajaran Dogma Gereja Katolik - F. Purwanto (Jurnal Orientasi Baru, 2012)
Prophetic function played important role in the Old Testament people as well as the people of New Testament. A prophet is a person who have particular gift to proclaim the will of God. Jesus is known as a great prophet by the people. His prophetic role leads Him to offer Himself to death, though He was raised by God afterward. It is true that prophetic function receded steadily in the ancient Church and the period that follows. But then, this function gradually regains its place in the service of the bishop as the guardian of the true apostolic faith. Particularity of the teaching of the bishop is that they teach authentically (LG 25). One of their particular teaching is to teach qualified as dogma.